2019
DOI: 10.22207/jpam.13.4.63
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bacteria from the Gut of Blue Gourami (Trichogaster tricopters) and its Role on Growth

Abstract: Five variant groups were isolated from the gut of Blue gourami Trichogaster tricopterus through serial dilution, identified by using biochemical tests and bacteria were Bacillus sp., (G1) Pseudomonas sp., (G2) Enterobacter sp., (G3) Aeromonas sp., (G4) and Escherichia sp., (G5). Based on enzymatic productivity (Amylase, Cellulase, Lipase, and Protease) and antimicrobial activity Bacillus sp., Enterobacter sp., and Aeromonas sp., and mass multiplied using nutrient broth. Four different feeds such as feed I (Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…The Feed Conversion Ratio (FCR) of blue gourami was lower in feed IV (4·46 ± 0·53) and higher in feed I (8·41 ± 0·23) (Deepika et al . 2019). Somrudee Silarudee et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Feed Conversion Ratio (FCR) of blue gourami was lower in feed IV (4·46 ± 0·53) and higher in feed I (8·41 ± 0·23) (Deepika et al . 2019). Somrudee Silarudee et al .…”
Section: Resultsmentioning
confidence: 99%
“…and lower feed I (control) (6Á3 AE 0Á05). Deepika et al (2019) reported that the feed consumption of blue gourami was higher in feed IV (5Á4 AE 0Á13) containing 1 ml each of Bacillus sp., Enterobacter sp., Aeromonas sp. and lower in the feed I (control) (3Á1 AE 0Á41).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peranan bakteri yang menguntungkan dalam saluran pencernaan yang memiliki potensi menghasilkan enzim pencernaan eksogen telah banyak diteliti. Hasil riset Deepika et al, (2019) menyatakan bahwa salah satu jenis bakteri pada saluran pencernaan ikan Gurami adalah Bacillus sp. yang dapat menghasilkan enzim hidrolitik seperti protease, amylase, selulase dam lipase.…”
Section: Pendahuluanunclassified